Implementation Of The Workload Indicators Of Staff Needing Method Based On Workload To Determine The Right Number Of Human Resources Requirements At The Medical Rehabilitation Poly Of H.Abdul Manan Simatupang Kisaran Hospital In 2021 - Pratama Putra Nasution; Chrismis Novalinda Ginting; Tan Suyono; Sri Lestari Ramadhani Nasution (International Journal of Health and Pharmaceutical (IJHP), 2023)
A good work program is needed by using the WISN (Workload Indicators of Staff Needing) method, which helps see the workload given to and received by medical workers in health facilities. This study aims to determine the appropriate number of employees using the WISN (Workload Indicators of Staff Needing) method to reduce the workload in the hospital's medical rehabilitation polyclinic. This research is a descriptive study with quantitative data analysis conducted at the H. Abdul Manan Simatupang Hospital in 2021. The data taken is medical record data on the total number of patient visits at the medical rehabilitation polyclinic and staffing data for the rehabilitation polyclinic. H. Abdul Manan Simatupang Kisaran Hospital. We found a relatively high number of visits at the Medical Rehabilitation Polyclinic; the workforce data obtained totaled four employees who handled patients directly. The study's results found that the available work time was not directly proportional to the existing standard workload, where the available work time is 135,360 minutes per year while the Standard Workload is 347,424 minutes per year. The workload in the Medical Rehabilitation Polyclinic is too high, and we can obtain the cause from the number of operational staff on duty.